Design Optimization and Application of Hybrid Bit to Reduce a Well Cost in Geothermal Field - Muhammad Taufiq Fathaddin; Fakhri Ade Andika; Ratnayu Sitaresmi (Universitas Islam Riau (UIR) Press, 2020)
Hybrid bit is one of the innovations developed for very hard and abrasive formations such as in geothermal field. This bit eliminates the risk of losing cones, reduces tripping time, and increaseas ROP to reduce the well cost. The stage of data processing by calculating the UCS formation using D-BOS software and design optimization based on 9-7/8